The Religious Life Harmony and the Nation’s Integrity in History View - Budiwati, Neti (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2012)
In addition to a multi-ethnic and multi-cultural, Indonesian people’s life is also multi-religion/beliefs. This plural living conditions is prone to conflict. Most conflict happened is often ridden by religious issues and sentiments. Such circumstances should not be avoided to maintain the national integration. Plural life should be maintained in order to realize the the harmony of life in a multi-ethnic, multi-cultural, and multi-religious society.Therefore, the government issued UU Kerukunan Hidup Beragama (the Law on Religious Life Harmony) to achieve harmony in the society’s life. In addition, one alternative to consider is to develop a civil society that is the embodiment of the nation as the realization of developing a nation that is advanced in every sector of development. The establishment of civil society must be understood as an aspiration to realize the democratic and infependent modern nation among the hustle and bustle of the differences. An ideal civilization will be able to build a nation with significant progress. The perspective of civil society in Indonesia is simple, to build a fair, open, and democratic society upon the foundation of the Almighty God. Therefore, to be developed in this kind of life is the constructive pluralism, which can be developed through multicultural education.